Synthesis and characterization of RFeO3: experimental results and theoretical prediction. Issue 4 (2nd October 2018) - Kamal Warshi, M.; Mishra, Vikash; Sagdeo, Archna; Mishra, Vinayak; Kumar, Rajesh; Sagdeo, P.R.
Abstract: Detailed structural analysis of rare-earth orthoferrites RFeO3 (R = La, Pr, Nd, Sm, Eu, Tb, Dy, Y, Ho, Er, and Yb) has been reported. Polycrystalline samples of RFeO3 were prepared using the sol-gel method. Structural phase purity of the prepared samples has been investigated using synchrotron X-ray diffraction (SXRD) technique and structural distortion has been estimated using the refinement of SXRD data in terms of Fe–O–Fe bond angles, Fe–O bond lengths, and FeO6 octahedra distortions. It is observed that with the increase in the ionic radii of R site cation, the lattice constants, R–O bond length, and Fe–O–Fe bond angles increase; whereas Fe–O bond length almost remains constant. The FeO6 octahedra tilt angles ϕ along (001) direction and θ along (110) direction decrease with increasing ionic radius of R site cations. The structural distortion-parameters of RFeO3 samples obtained from refinement and compared with the results extracted from modern Bond Valance Sum model (SPuDS) and with density functional theory using WIEN2k package and found consistent with experimental results. The possible correlation between the structural and other physical properties such as transition temperature obtain from differential scanning calorimetry (DSC) has been investigated.